The physiological capacity of the world`s highest ranked female cross-country skiers - Sandbakk, O.; Hegge, A. M.; Losnegard, T.; Skattebo, Ø.; Tonnesen, E.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2016)
Purpose: The objective of this study is to compare the physiological capacity and training characteristics of the world`s six highest ranked female cross-country skiers (world class (WC)) with those of six competitors of national class (NC).